Reliability evaluation of electricity-heat integrated energy system with heat pump - Shenxi Zhang; Min Wen; Haozhong Cheng; Xiao Hu; Guodong Xu (CSEE Journal of Power and Energy Systems, 2018)
Integrated energy system (IES) has the advantages of improving the efficiency of energy utilization and promoting the consumption of renewable energy. It is of great importance to evaluate the reliability of an IES. This paper proposes a novel reliability evaluation method for the electricity-heat IES with heat pump. First, the load-point reliability indices and system-level reliability indices are defined according to the characteristics of electricity-heat IES. Second, the model of maximum output heat power of heat pump at the user-side considering the safety criterion of distribution network is established, and the step-varied repeated power flow method is applied to solve the model. Third, the reliability evaluation procedure of electricity-heat IES with heat pump based on the Monte Carlo simulation is presented. Case studies are carried out on the electricity-heat IES of an industrial park, and the results show that the configuration site, capacity and coefficient of performance of heat pump as well as the security constraints of distribution network can significantly affect the reliability indices.